Assay of von Willebrand Factor (vWF)-cleaving Protease Based on Decreased Collagen Binding Affinity of Degraded vWF - Gerritsen, Helena E.; Turecek, Peter L.; Schwarz, Hans P.; Lämmle, Bernhard; Furlan, Miha (Thrombosis and Haemostasis, 1999)
Patients with thrombotic thrombocytopenic purpura (TTP) have a deficiency of von Willebrand factor (vWF)-cleaving protease, whereas patients with hemolytic-uremic syndrome (HUS) show normal activity of this protease. Present methods for assaying vWF-cleaving protease by immunoblotting are time-intensive and cumbersome. We therefore developed a new functional assay based on the preferential binding of high-molecular-weight forms of vWF to collagen. In this assay, the diluted plasma sample to be tested is added to normal human plasma in which protease activity had been abolished. The vWF present in the protease-depleted plasma is digested by the vWF-cleaving protease in the test plasma. The proteolytic degradation leads to low-molecular-weight forms of vWF, which show impaired binding to microtiter plates coated with human collagen type III. The collagen-bound vWF is quantified using a peroxidase-conjugated rabbit antibody against human vWF. The values of vWF-cleaving protease activity in tested plasma samples are read from a calibration curve achieved by incubating the vWF-substrate with dilutions of a normal human plasma pool (NHP). Testing of plasma from patients with TTP and HUS showed that the assay can be used to distinguish between these two syndromes. The presence of an inhibitor can be detected by carrying out the test after incubation of NHP with the patient plasma sample, thus enabling differentiation of patients with familial TTP from those with non-familial TTP.
Keywords: von Willebrand factor-cleaving protease; collagen binding assay; TTP; HUS